Reducing Turnover Costs through Engagement: The Role of Workplace Relationships and Meaningful Work at BNI KC Cilegon - Adhithara, Firman; Rahmawati, Putu Indah; Heryanda, Komang Krisna (Yayasan Riset dan Pengembangan Intelektual, 2025)
This study examines the role of employee engagement in reducing implicit turnover costs by enhancing workplace relationship quality and meaningful work. The research is motivated by inconsistencies in prior findings—some studies report a significant negative effect of employee engagement on intention to leave, while others find no significant relationship. Additionally, employee engagement has been explored as a mediating variable between workplace relationship quality and meaningful work on intention to leave, with mixed results. The study was conducted at BNI KC Cilegon (Persero) Tbk, involving 166 respondents. Data were analyzed using the Partial Least Squares (PLS) method via AMOS software. The findings reveal that workplace relationship quality has a significant direct effect on intention to leave. Furthermore, meaningful work serves as a partial mediator, while employee engagement fully mediates the relationship between the predictors and intention to leave. These findings highlight the strategic importance of fostering positive workplace relationships and creating meaningful work experiences. Such efforts not only enhance employee engagement but also reduce turnover intentions, thereby supporting organizational cost-efficiency and long-term sustainability.